Modernologies : contemporary artists researching modernity and modernism - Breitwieser, Sabine; MACBA (Museu d'Art Contemporani de Barcelona), Barcelona; Muzeum Sztuki Nowoczesnejw, Warszawie (Barcelona : MACBA (Museu d'Art Contemporani de Barcelona), 2009)
Artaker, Anna ; Creischer, Alice ; Siekmann, Andreas ; Eydel, Katja ; Ferreira, Angela ; Fraser, Andrea ; Genzken, Isa ; Graham, Dan ; Hurst, Robin ; Holert, Tom ; Honecker, Claudia ; Hugonnier, Marine ; IRWIN ; Islam, Runa ; Klub Zwei ; Knight, John ; Labor k3000 ; Lawler, Louise ; Maljkovic, David ; Margreiter, Dorit ; Matta-Clark, Gordon ; Metzger, Gustav ; Müller, Christian Philipp ; Olesen, Henrik ; Olowska, Paulina ; Pisano, Falke ; Poledna, Mathias ; Pumhösl, Florian ; Rosler, Martha ; Tudela, Armando Andrade ; Osten, Marion von ; Willats, Stephen ; Williams, Christopher
Biog., ind. tent., gr. tent., bibliog. p. 223-228, biog. auteurs p. 229
Engels
Published on the occasion of the exhibition "Modernologies : contemporary artists researching modernity and modernism at MACBA (Museu d'Art Contemporani de Barcelona) in Barcelona, 23.09.2009 - 17.01.2010 and at Muzeum Sztuki Nowoczesnejw in Warszawie, febr. - march 2010
boek